H‐ficolin binds Aspergillus fumigatus leading to activation of the lectin complement pathway and modulation of lung epithelial immune responses. Issue 2 (24th August 2015) - Bidula, Stefan; Sexton, Darren W.; Yates, Matthew; Abdolrasouli, Alireza; Shah, Anand; Wallis, Russell; Reed, Anna; Armstrong‐James, Darius; Schelenz, Silke
Summary: Aspergillus fumigatus is an opportunistic fungal pathogen that typically infects the lungs of immunocompromised patients leading to a high mortality. H‐Ficolin, an innate immune opsonin, is produced by type II alveolar epithelial cells and could participate in lung defences against infections. Here, we used the human type II alveolar epithelial cell line, A549, to determine the involvement of H‐ficolin in fungal defence. Additionally, we investigated the presence of H‐ficolin in bronchoalveolar lavage fluid from transplant patients during pneumonia. H‐Ficolin exhibited demonstrable binding to A. fumigatus conidia vial ‐fucose, d ‐mannose and N ‐acetylglucosamine residues in a calcium‐ and pH‐dependent manner. Moreover, recognition led to lectin complement pathway activation and enhanced fungal association with A549 cells. Following recognition, H‐ficolin opsonization manifested an increase in interleukin‐8 production from A549 cells, which involved activation of the intracellular signalling pathways mitogen‐activated protein kinase MAPK kinase 1/2, p38 MAPK and c‐Jun N‐terminal kinase. Finally, H‐ficolin concentrations were significantly higher in bronchoalveolar lavage fluid of patients with lung infections compared with control subjects ( n = 16; P = 0·00726). Receiver operating characteristics curve analysis further highlighted the potential of H‐ficolin as a diagnostic marker for lung infection (area under the curve = 0·77; P < 0·0001). Hence, H‐ficolin participates in A. fumigatus defence through the activation of the lectin complement pathway, enhanced fungus–host interactions and modulated immune responses.